Sustainable Fish Cage Aquaculture in Cirata Reservoir West Java, Indonesia: A System Dynamics Approach - Gunawan, Wawan; Hasan, Zahidah; Tasrif, Muhammad (Prabandhan: Indian Journal of Management, 2011)
The aims of this research were to identify and analyze processes causing fish productivity dynamic, to construct the model, and to design policy for sustainable Floating net cage aquaculture (FNCA) using system dynamics approach. The result of this research showed that the acceleration policy scenario gave a better performance in fish productivity and water quality than that in eutrophication policy scenario. On the other hand, the acceleration policy scenario created the higher fish stocking density, environmental cost and fish price than the eutrophication scenario. The simulation showed that fish productivity fluctuated by changing some importance parameters of the model such as FNCA unit regulation, aeration and change of fish stocking density.